The Effect of Collaborative Learning Model on Mathematics Problem Solving Ability Tritech Informatika Vocational School Students Medan T.P 2021/2022 - Harahap, Yeni Sahfitri; Harahap, Tua Halomoan (EduMatika: Jurnal MIPA, 2022)
This study aims to determine the effect of the use of collaborative learning learning models on student problem solving. Students are given a test to see how the results of students' mathematical problem solving. Response, and student activities towards learning. Then the researcher described the results in data analysis. The method used by the researcher is a pre-experimental method using a one group pretest-posttest design. This research was conducted at SMK Tritech Informatika Medan in class X- Multimedia Executive as many as 25 students. The results of hypothesis testing conducted in this study indicate that the t-count value is 16.4037 with the t-table value at a significant level = 0.5, which is 2.060, meaning that the t-count value > t-table value or 16.4037 > 2.060. So Ha is accepted and H0 is rejected. It can be concluded that there is a significant influence on the Collaborative Learning learning model on the mathematical problem solving abilities of the students of SMK Tritech Informatikan Medan.